Solar bikes: user acceptance understanding user experience, preference and acceptance - Pauline van den Berg; Theo Arentze; Karst Geurs (Spool, 2017)
Car traffic causes carbon emissions and air pollution and has negative effects on public health and quality of life in cities. Solar bikes are an innovative, sustainable transport option that can offer a substitute for car travel. Solar bikes are electric bikes with solar cells that are powered by the sun. This expands their range compared to regular e-bikes as the bikes are charged during the trip and at the destination without electricity. The aim of this project is to understand people’s preferences, conditions for acceptance and experiences with the solar bike. Insight in preferences and experiences will assist urban policy makers in identifying which interventions in the built environment can stimulate the acceptance and use of solar bikes.